Apakah Pendidikan Lingkungan Merupakan Faktor Utama Pembentuk Perilaku Lingkungan pada Masyarakat di Negara Berkembang? - Nova - Ulhasanah (Universitas Andalas, 2019)
Environmental education in developed countries is currently being intensively developed to increase the environmental awareness of the community in order to achieve sustainable development. But for developing countries like Indonesia, is environmental education the most urgent thing to do first to improve the successful implementation of environmental management system? This paper presents an analysis of social aspects related to the environmental behavior of a society, which is about the importance of the